Tinggalan Arkeologi Di Kerajaan Gowa Dan Tallo Berdasarkan Kajian Geologi Dan Lokasi Sumber Bahan - Fadhlan S. Intan (Berkala Arkeologi, 1995)
The role of geology in the study of archeology is very important, where it can describe problems related to the state of the natural environment, the acquisition of raw material sources, rock elements as a constituent of an ancient building and other ancient environments. Based on the foregoing, this paper will describe in addition to the geological conditions, as well as the extent to which the use and location of rock extraction as raw material for archaeological data in the Kingdoms of Gowa and Tallo.